Bearing-Based Formation Control and Network Localization via Global Orientation Estimation - Trinh, M.H.; Lee, B.H.; Ye, Mengbin; Ahn, H.S. (2018)
Consider a system of single-integrator agents in the d-dimensional space whose goal is to achieve a target formation shape specified by some desired bearing vectors. Suppose that the agents do not share a common global reference frame but can sense the relative orientations and bearing information with regard to some neighbor agents. We propose solutions to two problems: global orientation estimation and bearing-only measurement based formation control. Combining the solutions to the two problems, we solve the distributed bearing-based formation control problem. The combined strategy guarantees the desired formation shape is almost globally achieved up to a translation, a rotation and a scaling. Furthermore, we apply the proposed strategy to bearing-based network localization as a dual problem.